2005
DOI: 10.1021/ja043918p
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Effects, Dynamics, and the Mechanism of Solvolysis of Aryldiazonium Cations in Water

Abstract: The mechanism of the heterolytic solvolysis of p-tolyldiazonium cation in water was studied by a combination of kinetic isotope effects, theoretical calculations, and dynamics trajectories. Significant (13)C kinetic isotope effects were observed at the ipso (k(12)C/k(13)C = 1.024), ortho (1.017), and meta (1.013) carbons, indicative of substantial weakening of the C(2)-C(3) and C(5)-C(6) bonds at the transition state. This is qualitatively consistent with a transition state forming an aryl cation, but on a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 72 publications
(73 reference statements)
4
29
0
1
Order By: Relevance
“…From the combined experimental results and simulations, they found that the energy flow within the alkyl side-chain could be reasonably well represented by a first-order process having a rate coefficient of ~4×10 11 s -1 . In their second study, 124 Singleton's group again combined theory and experiment to model a solution-phase reaction. The reactant in this case was an aryldiazonium cation, which was undergoing nucleophilic substitution of the nitrogen by water.…”
Section: Trajectory Calculations For Solution-phase Reactionsmentioning
confidence: 99%
“…From the combined experimental results and simulations, they found that the energy flow within the alkyl side-chain could be reasonably well represented by a first-order process having a rate coefficient of ~4×10 11 s -1 . In their second study, 124 Singleton's group again combined theory and experiment to model a solution-phase reaction. The reactant in this case was an aryldiazonium cation, which was undergoing nucleophilic substitution of the nitrogen by water.…”
Section: Trajectory Calculations For Solution-phase Reactionsmentioning
confidence: 99%
“…A mechanism at the S N 2Ar/S N 1 boundary was proposed for the nucleophilic substitution reaction of aryldiazonium ions in water [86].…”
Section: Concerted/stepwise Boundarymentioning
confidence: 99%
“…2 Thus far, the intermediates known to exhibit such behavior are singlet biradicals, 3 radical cations, 4 radicals, 5 and carbocations. 6 In the present study, we sought to investigate whether carbene chemistry might also be subject to these dynamical effects.…”
Section: Discovery Of Apparent Nonstatistical Dynamics For a Wolff Rementioning
confidence: 99%